Analisa Kandungan SiO2, CaO, dan MgO dalam Pasir Menggunakan Cara Kerja SNI 2049:2015 - Alfikri, M.; Amran, Ali (Lembaga Yasin AlSys, 2026)
The analysis of mineral oxide content in sand plays an important role in determining the quality of raw materials for the chemical and construction materials industries, yet the application of conventional methods based on national standards remains relatively limited compared with the use of modern instruments. This study aimed to analyze the content of silicon dioxide (SiO₂), calcium oxide (CaO), and magnesium oxide (MgO) in sand using a gravimetric method in accordance with the SNI 2049:2015 procedure. A quantitative approach with a laboratory experimental design was employed, in which sand samples were analyzed through successive stages of dissolution, precipitate separation, ignition, titration, and weighing of the pure compound residues. Data were obtained from gravimetric and volumetric measurements and were analyzed quantitatively based on the stoichiometric relationships of the chemical reactions. The results showed that the SiO₂ content reached 84.0%, while CaO and MgO were 1.16% and 1.13%, respectively, indicating the dominance of silica in the sand composition with relatively low levels of basic oxides. These findings confirm that the gravimetric method based on the national standard is capable of producing accurate and consistent data for sand mineral characterization, thereby reinforcing the potential use of sand as a raw material for high-silica-based industries.